PERLINDUNGAN KONSUMEN MELALUI KEWAJIBAN SERTIFIKASI HALAL BAGI PELAKU USAHA MIKRO DAN KECIL BERDASARKAN PERPPU NO. 2 TAHUN 2022 TENTANG CIPTA KERJA - Djuhrijjani Djuhrijjani (Lensa, 2023)
Indonesia is a country with a Muslim majority. The state must be able to provide protection to its citizens to carry out religious teachings. One of the obligations of Muslims is to consume halal food/drinks. Consumer Protection Law No. 8/1999 then Law no. 33/2014 concerning Halal Product Guarantee is access for Muslim consumers to obtain halal products. This regulation is important because Muslim consumers are a very potential market that can affect the economy. UU no. 33/2014 including the law amended by the omnibus Law no. 11/2020 concerning Job Creation. However, this regulation did not last long. On December 30, 2022, the government issued Government Regulation in Lieu of Law (Perppu) No. 2 of 2022 concerning Job Creation which revokes Law no. 11 of 2020 concerning Job Creation. In the previous arrangement there was a policy of halal certification for micro and small business actors free of charge through a business actor's statement. This free certification is to accelerate the protection of Muslim consumers in terms of obtaining halal products. This study uses normative qualitative methods using secondary data. From the results of this study, it was concluded that there are very substantial differences related to the meaning of halal certificates which affect the process of applying for halal certification by micro and small business actors, as well as the possibility of the validity period of halal certificates forever.